Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists -- including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan -- whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art

Lessons from the intersexed - Kessler, Suzanne J. (Rutgers University Press, 1998)
From the moment intersexuality-the condition of having physical gender markers (genitals, gonads, or chromosomes) that are neither clearly female nor male-is suspected and diagnosed, social institutions are mobilized in order to maintain the two seemingly objective sexual categories. Infants' bodies are altered, and what was "ambiguous" is made "normal." Kessler's interviews with pediatric surgeons and endocrinologists reveal how the intersex condition is normalized for parents and she argues that the way in which intersexuality is managed by the medical and psychological professions displays our culture's beliefs about gender and genitals. Parents of intersexed children are rarely heard from, but in this book they provide another perspective on reasons for genital surgeries and the quality of medical and psychological management. Although physicians educate parents about how to think about their children's condition, Kessler learned from parents of intersexed children that some parents are able to accept atypical genitals. Based on analysis of the medical literature and interview with adults who had received treatment as interesexed children, Kessler proposes new approaches for physicians to use in talking with parents and children. She also evaluates the appearance of a politicized vanguard, many of who are promoting an intersexual identity, who seek to alter the way physicians respond to intersexuality. Kessler explores the possibilities and implications of suspending a commitment to two "natural" genders and addresses gender destabilization issues arising from intersexuality. She thus compels readers to re-think the meaning of gender, genitals, and sexuality.
Keywords: LGBTQIA2+; approches et analyses; capacitisme; care; corps; cours; discipline; ethnographie; intersexuation; premier cycle; psychologie; santé; sciences humaines; soc2014; système de genre; systèmes d'oppressions; thématiques; violences; violences médicales